The digital war of ISIS (Journal of the College of Basic Education, 2022)
Terrorism in all its forms invaded the entire world, threatening its security and stability, and hindering development of all kinds. The repercussions of the events in Syria and the setback in Mosul led to the emergence of a third generation of hardline Salafis, different from what preceded it in thought and methodology. The emergence of the Islamic State in Iraq and the Levant, known as the organization ISIS, serious repercussions on the Iraqi, regional and global arena.